Overview of shopping malls ventilation and air conditioning energy-efficient system control needs - P.O.; О.M. (Технічна інженерія, 2022)
The article is devoted to the analysis of design-specific features and microclimate control problems searching of the shopping malls. The main trends of shopping malls development are formulated. It is shown that Fagner indices and ISO 7730: 2005, ISO 10551: 2019 standards are used to evaluate human comfort indoors. It has been established that improper usage of shopping malls ventilation can be a cause of visitors’ and employees’ illnesses. It was found that parameters that need to be controlled are not limited to typical like temperature and humidity. It is proposed to make measurements of the following parameters: carbon monoxide, PM2.5 and PM10 particles, carbon dioxide (CO2), formaldehyde (HCHO), volatile organic compounds (TVOC). It is shown that human comfort in the shopping mall creation is an important task that needs to be solved in conjunction with energy saving. The main parameters of the microclimate that should be used in system control synthesis are given. The main shopping malls devices of technological processes automation control manufacturers are presented. It is emphasized that energy efficiency approaches are divided into constructive and algorithmic. The constructive approaches implementation is possible only if the shopping center was built in compliance with all regulatory requirements of premises construction. A review of control laws and modeling methods that are used in heating and ventilation systems control is provided. The basic principles of energy resources saving are formulated. It is determined that shopping center is an object with distributed parameters due to its size and separate conditions for each room creation needs. It is shown that classical approaches that are proposed to be used for temperature and humidity processes of the object with distributed parameters control are not suitable for its energy efficiency.